Sūkās VII. The Near Eastern Pottery and Objects of Other Materials from the Upper Strata - Buhl, Marie-Louise (1983)
= Det Kongelige Danske Videnskabernes Selskab Historisk-filosofiske Skrifter, Bind 10, Nr. 4; Kommissionaer: Munksgaard. Kr. 200,-.